Analysis of Self-Regulation in the Rencong Telang Islamic Society Perspective of Social Cognitive Theory - Agustina, Linda; Zainuddin, Mahli (Universitas Ahmad Dahlan, 2023)
The Rencong Telang Islamic society reflects distinctive cultural characteristics and unique values, particularly in the self-regulation system involving religious norms and local traditions. The individual's ability to control behavior and adapt to societal values is a key element in understanding behavior, especially in social and religious contexts. This research aims primarily to delve into and comprehensively analyze the phenomenon of self-regulation in the Rencong Telang Islamic society. Specific objectives include exploring the concepts and practices of self-regulation, involving religious norms, local traditions, and cultural values that shape self-regulation. This article also aims to analyze the role of self-regulation in various aspects of community life, ranging from worship to marriage customs and communal land management. Focus is also given to the social challenges and changes faced by the Rencong Telang Islamic society to understand how self-regulation can uphold traditional values. The method used is literature review, encompassing an analysis of relevant literature on self-regulation, Islamic society, and the specific context of the Rencong Telang Islamic society. The research findings indicate that self-regulation in this society encompasses various aspects of daily life, involving customs, Islamic principles, and governance. The ability to control behavior in worship, marriage customs, and communal land management is an integral part of self-regulation. The community employs self-regulation to preserve traditional values, adapt to changes, address social challenges, and manage social interactions. In the context of Social Cognitive Theory, self-regulation is explained as the result of behavioral control in customs and Islamic beliefs, embodied in Undang as the daily norm reflecting the influence of nature, Islamic teachings, and local traditions. Overall, self-regulation in this society is not solely individual but reflects social dynamics involving the entire community, with significant impacts on aspects of life, customs, Islam, and governance, playing a crucial role in preserving cultural values and identity.